Implementasi Kurikulum Darurat Madrasah di MAN I Kota Kediri - Ahmad Ainur Rofiq; Zaenal Arifin (Institut Agama Islam Tribakti (IAIT) Kediri, 2021)
Covid-19 is a type of infectious virus that has spread widely in Indonesian society, this has resulted in changes in the lives of Indonesian people, including in the field of education. The government has initiated a madrasah emergency curriculum policy that can be applied in learning activities. This research activity is intended to find out how the planning activities, implementation activities and evaluation activities of the madrasa emergency curriculum at MAN I Kediri City are. This study uses a descriptive qualitative approach. The results of this study are; the implementation of the emergency curriculum has not run perfectly, this is due to the lack of facilities and the lack of understanding of IT from both educators and students.